2010
DOI: 10.1002/jpln.200700280
|View full text |Cite
|
Sign up to set email alerts
|

Is thermal oxidation at different temperatures suitable to isolate soil organic carbon fractions with different turnover?

Abstract: Findings of previous studies suggest that there are relations between thermal stability of soil organic matter (SOM), organo-mineral associations, and stability of SOM against microbial decay. We aimed to test whether thermal oxidation at various temperatures (200°C, 225°C, 275°C, 300°C, 400°C, or 500°C) is capable of isolating SOM fractions with increasing stability against microbial degradation. The investigation was carried out on soils (Phaeozem and Luvisol) under different land-use regimes (field, grassla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…4). Similarly, other studies have found no clear correlation between thermal stability and SOC degradability using isotopic analysis and different thermal techniques such as the TG‐DSC method ( Kuzyakov et al, 2006; Dorodnikov et al, 2007) or other thermal oxidations methods ( Helfrich et al, 2010) at similar temperatures. Kuzyakov et al (2006) used TG‐DSC to study the thermal stability of SOC in only one soil (loamy Gleyic Cambisol) which had been cultivated with Miscanthus for 10.5 years.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…4). Similarly, other studies have found no clear correlation between thermal stability and SOC degradability using isotopic analysis and different thermal techniques such as the TG‐DSC method ( Kuzyakov et al, 2006; Dorodnikov et al, 2007) or other thermal oxidations methods ( Helfrich et al, 2010) at similar temperatures. Kuzyakov et al (2006) used TG‐DSC to study the thermal stability of SOC in only one soil (loamy Gleyic Cambisol) which had been cultivated with Miscanthus for 10.5 years.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies demonstrated a relationship between thermal and biological stability of SOC for pyrolysis ( Leinweber and Schulten 1992; Plante et al, 2005; Gregorich et al, 2015) and thermal oxidation ( Siewert , 2001; Lopez‐Capel et al, 2005; Peltre et al, 2013). However, other studies found no consistent relationship ( Dorodnikov et al, 2007) or even no relationship ( Kuzyakov et al, 2006; Helfrich et al, 2010) using thermal oxidation. Despite these contradictory findings, thermal oxidation techniques have been used in recent studies to determine biologically labile and stable pools of SOC in mineral soils ( Gregorich et al, 2015; Katsumi et al, 2016; Ma et al, 2016; Miao et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…An improved characterisation -both chemical and functional -of the individual fraction is needed (Gregorich et al 2006, Broos et al 2007, Helfrich et al 2009, Prechtel et al 2009). …”
Section: Resultsmentioning
confidence: 99%